CORE STABILITY EXERCISES LEBIH MENINGKATKAN AKTIVITAS FUNGSIONAL PADA NYERI PUNGGUNG BAWAH MIOGENIK - Nur Susanti (LPPM Universitas Pekalongan, 2015)
Myogenic low back pain `is located around low back area. It is caused by musculoscletal disorders without neurologic disorders from twelve thoracal vertebrae to the hip. It is caused by static and dynamic factors that is causing pain. Low back muscle spasms and its surroundings cause imbalance muscle activities. Therefore, it decreases instability of abdominal and low back muscles. Limitation of lumbar movement decreases functional activities. Physiotherapy is intended to relief the pain and more relaxation for hospitalized patience. Meanwhile, core stability exercisesareto increase functional activities by moving transversus abdominis, multifidus, diafragma, and pelvic floor muscles. The research was aimed at testing core stability exercises forimproving myogenic functional activities. The research was designed as a quasi eksperimental by using pre-test andpost-test design with control group. The research was held at RSUD Bendan Pekalongan Physiotherapy installation. The research subject covered 28 patients. Measurement of functional activities of myogenic low back pain was conducted by using oswestry disability questionnaire (ODQ) before and after exercises. It was divided into two groups as the control and treatment group. Control and treatment group was three times a week. The result of this research was the increasing of ODQ score of control group for p<0.05, and p<0.05 for treatment group. It means that control group and treatment group can improve functional activities of myogeniclow back pain. Comparation test of data by using independent test is p<0.05, whether before and after exercise. The average of control group is 8.14%. The average treatment group is 28.57%. It is meant that treatment group is good for improving functional activities than control group. The research conclusion was that core stability exercises training improv the functional activities in basic therapy of myogeniclow back pain. It is expected that core stability exercises and basic therapy can be used in patient with myogeniklow back pain to improve of functional activity.